Socialization Of Utilization Of Local Potentials In Tourism Village Planning Effort In Selaawi Village, Garut Regency - Halvi Aulia; Zahara Oetari; Dodi Yudiardi; Galih Abdul Fatah Maulani; Wildan Mukholad Nurfaisal; Afrizaldi Hendarsyah; Abdul Aziz Pardon (Indonesian Journal of Community Empowerment (IJCE), 2021)
Abstract This journal discusses the use of local potential in planning a tourism village in Selaawi village, Garut district. The method used in this activity is a seminar using the method of giving and discussing as well as direct observation to various places that have the potential to become tourist attractions. The method of implementing this activity is through several stages, namely initial survey, seminar, mentoring, monitoring and evaluation. With the socialization of this tourist village, it is hoped that it can increase public awareness and enthusiasm for tourism, besides that we know that Selaawi village has a high potential to become a tourist village seen from the local potential that exists in Selaawi village, especially Buskom Cius and Bonwi. Abstrak Jurnal ini membahas mengenai sosialisasi pemanfaatan potensi lokal dalam upaya perencanaan desa wisata di desa Selaawi kabupaten Garut. Metode yang digunakan dalam kegiatan ini adalah seminar dengan menggunakan metode pemberian materi dan diskusi serta observasi langsung ke berbagai tempat yang memiliki potensi untuk dijadikan sebuah tempat wisata. Metode pelaksanakan kegiatan ini melalui beberapa tahapan yaitu survey awal, seminar, pendampingan, monitoring dan evaluasi. Dengan diadakannya sosialisasi desa wisata ini diharapkan dapat meningkatkan kesadaran dan semangat masyarakat akan wisata, selain itu kami mengetahui bahwa desa Selaawi memiliki potensi yang tinggi untuk menjadi desa wisata dilihat dari potensi lokal yang ada di desa selaawi terkhusus Buskom Cius dan Bonwi.